Coupled DEM-MBD-PRM simulations of high-pressure grinding rolls. Part 2: Investigation of roll skewing. (15th March 2022) - Rodriguez, Victor A.; Barrios, Gabriel K.P.; Tavares, Luís Marcelo
Highlights: DEM-MBD-PRM coupling simulations used to study roll skewing. Uneven feed regarding rate, top size and fracture energy causing skewing were studied. When uneven feed to the HPGR no longer occurs, simulations show that skewing ceases. Simulations show the application of differential pressure on the pistons to reduce skewing. Heterogeneity in force profile is higher when skewing is disabled. Abstract: Roll skewing is an integral part of the operation of most HPGR designs presently used and is the result of the system attempting to compensate for uneven reaction from the particle bed along the length of the rolls to the applied forces. Several studies in recent years have simulated HPGR performance using the discrete element method (DEM). However, even when coupled to multi-body dynamics (MBD), these simulations have been limited to the description of one-dimensional motion of the rolls. The present work uses a combination of DEM and MBD to describe two-dimensional motion of the floating roll, making predictions of HPGR operation under skewing possible. Simulation case studies were carried out of a pilot-scale HPGR considering the case of uneven feeding, besides cases in which the feed is segregated with respect to particle size and also strength, represented by different median particle fracture energies, fed to each section of the rolls. Results show that the force profile along the bed and the product fineness along the length of the rolls become more uniform if skewing is allowed in the presence of uneven feed.